Dirāsāt al-Aḥkām al-Islāmiyyah bi manẓūri ‘ilmu al-‘ijtimā’ - Muhammad Atho’ Mudzhar (Al-Jami'ah: Journal of Islamic Studies, 2000)
This article provides a study of Islamic law based on a sociological perspective. The author argues that such study is possibly done for religion in one sense because it is considered as a cultural and social phenomenon. Yet, in the context of Islamic law there are three research domains: (1) methodological aspects, (2) normative facets, and (3) sociological features. The objects that can be discussed in the eye of sociological approach would be the influence of Islamic law on the society and its development, the impact of social advancement on the understanding of Islamic law, the degree of community's practices of Islamic law, the way of community's interaction with legal discourses, and the social legal movements. To assure the research possibilities, the author offers several examples of the above-mentioned research entities.  [Artikel ini memaparkan Study Hukum Islam berdasarkan pada perspektif Sosiologi. Penulis beranggapan bahwa  tersebut dapat digunakan untuk penelitian agama yang dianggap sebagai fenomerca budaya dan sosial. Meski demikian, dalam konteks hokum .Islam, terdapat tiga wilayah penelitian yaitu: (1) aspek metodologi, (2) sisi normatif dan (3) gambaran sosiologis. Obyek-obyek yang dapat didiskusikan dalam pandangan pendekatan sosioJogi dapat berupa pengaruh hukum Islam terhadap masyarakat dan pembangunannya, dampak kemajuan sosial pada pemahaman hukum Islam, tingkat pengamalan hukum Islam dari masyarakat, cara interaksi sosial dengan diskursus hukum, dan gerakan sosial dalam bidang hukurn. Untuk meyakinkan kemungkinan-kemungkirnm riset, penulis mengemukakan beberapa contoh jenis riset tersebut di atas.]